2003
DOI: 10.1093/ndt/gfg043
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in a post-cardiac surgery population with acute renal failure requiring dialysis: does age make a difference?

Abstract: The outcome in the elderly requiring dialysis due to ARF post-cardiac surgery is comparable with the outcome in a younger population. No significant difference was found in severity of disease between the elderly and the younger. Variables predicting mortality in the elderly are the presence of MOF, mechanical ventilation and hypotension 24 h before starting RRT. These findings indicate that at the time the nephrologist is called for an elderly patient requiring dialysis due to ARF following cardiac surgery, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 18 publications
2
31
0
2
Order By: Relevance
“…While Chertow et al [7] demonstrated an evident relationship between the increase in age and the incidence of dialytic ARF, Van den Noortgate et al [19] did not find any significant difference in patients with ages equal to or greater than 70 years old, when compared to under 70-yearolds, in a retrospective study of 3736 adults. The current work did not show any relationship between ARF and age.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…While Chertow et al [7] demonstrated an evident relationship between the increase in age and the incidence of dialytic ARF, Van den Noortgate et al [19] did not find any significant difference in patients with ages equal to or greater than 70 years old, when compared to under 70-yearolds, in a retrospective study of 3736 adults. The current work did not show any relationship between ARF and age.…”
Section: Discussionmentioning
confidence: 92%
“…Several authors utilize the term "renal dysfunction" for non-dialytic ARF, defining it as the presence of serum creatinine increases of around 25 to 50% of the preoperative value and the term "renal failure" for patients with dialytic ARF [5][6][7][8][9]18,19]. Although it seems more objective, the definition of ARF based on dialysis also depends on the experience of the nephrology team, although defined classical criteria are followed.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6]8,10,11,14,16 Critical to prevention and therapy is identification of risk factors. Previous risk profiles were limited to single-center experi- ences with site-specific data fields and hence restricted generalization, small sample size without a validation cohort, and incomplete characterizations of patients.…”
Section: Discussion General Overview: Summarymentioning
confidence: 99%
“…42,43 Age, although a direct marker for underlying degenerative disease in many specific organ systems, has not always been identified as an independent predictor of renal dysfunction risk after cardiac surgery. 1,2,4,10,16 We have shown that arterial stiffening manifested by increased PP is an independent variable that portends increased perioperative renal dysfunction outcome and may be more discriminating than age per se. In another study, 48 ascending aorta atherosclerosis predicted postoperative renal dysfunction, with advanced age directly associated with atherosclerotic severity.…”
Section: Pp Hypertensionmentioning
confidence: 97%
“…The numbers of patients ages.60 years in Western Europe and the United States are projected to rise from 231 million in 2000 to 395 million in 2050 (2). The incidence of AKI in the elderly varies according to the population studied, but multiple studies have shown that the elderly are more susceptible to the development of AKI than younger patients (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%